Vocabulary acquisition using Duolingo in French language learning : a Malaysian context - Suziana Mat Saad,; Nur Ameera Abd Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Vocabulary can be considered as the foundation to develop overall target language proficiency. Having a rich vocabulary would mean better performance in the four language skills. However, general in-class activities are insufficient for effective vocabulary acquisition to occur. Limited vocabulary learned through in-class activities might halt the occurrence of effective language learning. With that in mind, this study aims to explore the use of Duolingo in acquiring vocabulary of French language. For this purpose, 21 students from Basic French 1 class in Universiti Kebangsaan Malaysia volunteered to use this app for 8 weeks. 3 instruments were used in collecting data: online interviews, tests and observations. The online interview was used to elicit the students’ perception towards the app, whereas the tests were administered thrice to measure their performances in vocabulary acquisition. Observations were also carried out thrice to monitor their learning process. The findings reported that the students had positive perceptions towards Duolingo. They claimed it to be user-friendly, convenient, and entertaining. The tests results showed an improvement in terms of French vocabulary acquisition and it was found that Duolingo used multiple ways in presenting and teaching French vocabulary. This study showed that Duolingo can be used in building and developing French vocabulary outside the classroom walls. It is also beneficial in complementing French language classes to help students build their confidence in using the language. Further studies are also needed to investigate the usage of Duolingo in learning different aspects of language such as grammar or communication amongst learners of French in Malaysia.